Optimization of Band Pass Filter for Variance Reduction in Determining The Solution of Moment Tensor and Focusing Mechanism with ISOLA-GUI Sequence of The Minahasa Peninsula Earthquake Date 28 September 2018 to 1 October 2018 - Anggono, Titi; Tarigan, Rio Rinaldo; Barus, Diana Alemin (Talenta Publisher, 2021)
Sulawesi is one of the islands in Indonesia with a high level of seismicity because there are many active faults, especially in the Minahasa Peninsula area. This study discusses the moment tensor solution and the focus mechanism in the Minahasa Peninsula region from 28 September 2018 to 1 October 2018 using the ISOLA-GUI program. This program is used to process seismic data from the three components recorded by the seismogram. The data used in this study were five earthquake events consisting of earthquake foreshock, earthquake mainshock, and earthquake aftershock. With the ISOLA program, data processing is carried out which includes: crustal models, event info, selecting earthquake recording stations, preparing raw data for defining seismic sources, calculating green functions with computations, performing inversions and plotting results. In the inversion, the frequency of the band pass filter is selected to obtain the optimal reduction variance. After processing, calculating and interpreting the plot results, a fault model is obtained for each earthquake event, namely strike-slip.Â